3x-2+2=6+2

Simple and best practice solution for 3x-2+2=6+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2+2=6+2 equation:


Simplifying
3x + -2 + 2 = 6 + 2

Reorder the terms:
-2 + 2 + 3x = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 3x = 6 + 2
3x = 6 + 2

Combine like terms: 6 + 2 = 8
3x = 8

Solving
3x = 8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '3'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| 5-(b+3)=-1+2(b-3) | | 13-(8x)+4x-(-12)= | | x^2+25x-300=0 | | 5x+2(5x-15)=60 | | -6v=-16v+30 | | 10-16x=-230 | | 4-6(4n+1)= | | x/4=x/5-7 | | 6(-2+7x)+4x=36-2x | | 2(2.5x-5)+2= | | -8a+10=-8(a+3) | | n=-3/8=1/8 | | 2+(5+y)=0 | | 9(-8-2p)= | | -4+8(p+4)=4(4p-1) | | 15-9/3=-9 | | 14x-14=16x | | 10-3a=40 | | 81[(5+3)-5]= | | Y^2-9y=-18 | | 4t+9= | | -4(5-4x)=-40+6x | | -7=a-7 | | 7(m-7)=28-4m | | 33-3n=-6(n-8) | | -17=15n-20 | | 11m+10=9m | | 60=log(x) | | 4=4x+9 | | -3(n-4)-3=3-(n+2) | | 7x+1=1+8x | | ab+5a-b-5=0 |

Equations solver categories